2019
DOI: 10.1002/cpe.5173
|View full text |Cite
|
Sign up to set email alerts
|

An opcode‐based technique for polymorphic Internet of Things malware detection

Abstract: The increasing popularity of Internet of Things (IoT) devices makes them an attractive target for malware authors. In this paper, we use sequential pattern mining technique to detect most frequent opcode sequences of malicious IoT applications. Detected maximal frequent patterns (MFP) of opcode sequences can be used to differentiate malicious from benign IoT applications.We then evaluate the suitability of MFPs as a classification feature for K nearest neighbors (KNN), support vector machines (SVM), multilayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Pajouh et al [11] took the opcode sequences as discriminating features in the Long Short Term Memory (LSTM) algorithm and got an accuracy rate of 98.18% on a dataset consisted of 281 ARMbased malware and 270 ARM-based benignware. Darabian et al [12] counted the number of occurrence of each opcode, and found that malware uses some particular opcodes more frequently than benignware. The experimental results showed that the classifier could reach an accuracy of 99% in ARMbased IoT samples.…”
Section: B Malware Detection and Malware Family Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pajouh et al [11] took the opcode sequences as discriminating features in the Long Short Term Memory (LSTM) algorithm and got an accuracy rate of 98.18% on a dataset consisted of 281 ARMbased malware and 270 ARM-based benignware. Darabian et al [12] counted the number of occurrence of each opcode, and found that malware uses some particular opcodes more frequently than benignware. The experimental results showed that the classifier could reach an accuracy of 99% in ARMbased IoT samples.…”
Section: B Malware Detection and Malware Family Classificationmentioning
confidence: 99%
“…As a result, assorted existing researches put focus on more efficient approaches based on static analysis, e.g., reverse engineering the binary programs of IoT malware [9]. In related work [10,11,12], experiment results with high detection rates are obtained by exploring the operation codes (opcodes) and control flow graphs (CFG) of the IoT malware. Nevertheless, these related work did not take factors such as the CPU architecture into consideration and the evaluation datasets suffer from drawbacks such as limited scale and class imbalance, which might result in biased results.…”
Section: Introductionmentioning
confidence: 99%
“…However, designing effective and efficient malware detection approaches poses several challenges and still has open issues [30], for example due to counter-malware detection efforts by malware authors and cyber criminals. There are three major approaches for analyzing malware: static, dynamic and hybrid [31,32], each of them with their own pros and cons. Trying to mitigate some of the drawbacks of current static, dynamic and hybrid malware detection approaches, multi-view learning is a promising solution.…”
Section: Privacy and Security In Smart Computingmentioning
confidence: 99%
“…Most mobile malware detection systems are focused on local file analysis [11]. Malware analysis involves two key techniques: static analysis and dynamic analysis [12]. Static analysis examines malware without actually executing it to find malicious characteristics or suspicious codes [13], while dynamic analysis (also known as behavior analysis) executes malware in a controlled and monitored environment to observe its behavior [14].…”
Section: Related Workmentioning
confidence: 99%